The role of emotions on risk preferences: An experimental analysis - Anna Conte; M. Vittoria Levati; Chiara Nardi (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2013)
In the last decades, there has been a large volume of research showing that emotions do have relevant effects on decision-making. We contribute to this literature by experimentally investigating the impact of four specific emotional states - joviality, sadness, fear, and anger - on risk attitudes. In order to do so, we fit two models of behaviour under risk: the Expected Utility model (EU) and the Rank Dependent Expected Utility model (RDEU), assuming several functional forms of the weighting function. Our results indicate that all emotional states instigate risk-seeking behaviour. Furthermore, we show that there are some differences across gender and across participants experience in lab experiments.
Keywords: D81; C91; D00; 330; emotions; risk aversion; structural models